The Standardization Of The Mangkuak Recipes In Koto Tangah District Padang City - Yolanda Jefrina; Wirnelis Syarif (Jurnal Pendidikan Tata Boga dan Teknologi, 2021)
The purpose of this study was to produce the best the standardization of the recipe for mangkuak cake in Koto Tangah District, Padang City to determine the ingredients, equipment, processing techniques and 5 analysis of quality indicator which are expected to cover shape, color, aroma, texture and taste. The background of the research is that ingredients used and processing techniques. The various of processing techniques produce different quality indicator. This type of research is a mixed method. The source of qualitative research were obtained from 10 people experts in processing mangkuak cake and quantitative data sources were obtained from the community of 10 trained panelists whoe were experts in making mangkuak cake and 5 limited panelists from expert of society making mangkuak cake. Qualitative data collection techniques include observation, interviews, documentation while quantitative data collection techniques include the organoleptic the questionnaire format. Based on the result of organoleptic test get quality indicator mangkuak cake, the shape (rounded and tidy), the color (of skin white color in upper and brown color in center), aroma (coconut milk and pandan leaf ), the texture (soft), the taste (tasty and sweet).